2006
DOI: 10.1111/j.1365-2249.2006.03165.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 is involved in the enhancement of human natural killer cell activity byLactobacillus caseiShirota

Abstract: SummaryWe conducted a placebo-controlled, cross-over trial to examine the effect of Lactobacillus casei Shirota (LcS) on natural killer (NK) cell activity in humans. NK cell activity exhibited a declining trend during the period of placebo ingestion, but NK cell activity increased after intake for 3 weeks of fermented milk containing 4 × × × × 10 10 live LcS. When human peripheral blood mononuclear cells were cultured in the presence of heat-killed LcS, NK cell activity was enhanced. The ability of LcS to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 35 publications
4
127
0
3
Order By: Relevance
“…Therefore, we believe that the effect of 1073R-1 yoghurt is mainly dependent on the immunostimulatory polysaccharides produced from L. bulgaricus OLL1073R-1. However, the cell body of L. bulgaricus OLL1073R-1 may also contribute to the effect of this yoghurt because the cell body has been reported to exert host-mediated anti-tumour activity in mice (8) and some probiotics have been shown to enhance natural killer cell activity in elderly individuals (5,23,24) . With regard to natural killer cell activity, in the present study, we found a significant positive correlation between the promotion of natural killer cell activity and the total score for the 'eye/nose/throat' system, and these two parameters after intake were significantly higher in the 1073R-1 yoghurt group than in the milk group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that the effect of 1073R-1 yoghurt is mainly dependent on the immunostimulatory polysaccharides produced from L. bulgaricus OLL1073R-1. However, the cell body of L. bulgaricus OLL1073R-1 may also contribute to the effect of this yoghurt because the cell body has been reported to exert host-mediated anti-tumour activity in mice (8) and some probiotics have been shown to enhance natural killer cell activity in elderly individuals (5,23,24) . With regard to natural killer cell activity, in the present study, we found a significant positive correlation between the promotion of natural killer cell activity and the total score for the 'eye/nose/throat' system, and these two parameters after intake were significantly higher in the 1073R-1 yoghurt group than in the milk group.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that probiotics can regulate the expression of phagocytosis receptors in the neutrophils of healthy individuals and enhance natural killer cell activity. 18,31 In the present study, beneficial impact of probiotic bacteria is well established by statistical significant reduction in plaque index (PI) and level of Streptococcus mutans in Group-B (Probiotic group) as compared to Group-A (Control group). 2, 3 The observed improvement in clinical status may be attributed to the reduced levels of cariogenic as well as periodontal pathogens and effective colonization of the probioti bacteria within the oral cavity.…”
Section: Discussionmentioning
confidence: 83%
“…В конце периода наблюдения в группе, получавшей Bifidobacterium lactis BВ12, индекс SCORAD [первоначально равный 16 (7-25)] составил 0 (0-3,8), тогда как в группе, получавшей Lactobacillus GG, эта вели-чина равнялась 1 (0,1-8,7). Среди детей, получавших смесь без введения пробиотиков, индекс SCORAD соста-вил 13,4 (4,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)2). Таким образом, в данном исследо-вании показана не только эффективность пробиотиков для профилактики аллергии, но и более выраженное действие штамма Bifidobacterium lactis BВ12.…”
Section: обзор литературыunclassified